Application Of The Make A Match Learning Model To Improve Civics Education Learning Outcomes For Grade V Students At SDN 2 Trucuk - Kurniawati, Nina Dwi (Universitas Sebelas Maret, 2022)
This study aims to determine an increase in PPKn student achievement in grade V SDN 2 Trucuk through the application of the make a match method. This type of research is Classroom Action Research. The research subjects were 19 grade students in SDN 2 Trucuk, consisting of 10 male students and 9 female students. The object of research in the form of learning outcomes. Data were analyzed descriptively quantitatively. The results obtained by students at the beginning of the cycle are 71.4 with classical completeness of 62%. In the first cycle there was an increase in learning achievement, namely an average of 77 with completeness reaching 69%. In the second cycle the increase in learning achievement reached 84 with 88% completeness. Thus it can be concluded that the method of make a match can be used to improve the learning achievement of Civics in the fifth grade students of SDN 2 Trucuk Semester II in the academic year 2021/2022